al- ‘Urf and its applicability in Islamic deposit products - Bello, Shafii Abdul Azeez; Mohd Yasin, Norhashimah; Hassan, Rusni; Mohd Yazid, Zul Kepli (American Institute of Science, 2015)
Over the last decade Islamic banking has clear taken root. What began as novelty has made major strides. The main purpose of this paper was to explain the applicability of ‘urf in Islamic deposit products. This study set about the application of ‘urf in Islamic law briefly, moreover, the concept of deposit products in conventional bank just analysed while it in Islamic bank effectively analysed. The types of deposit products in both banks are chiefly current, saving and investment accounts. Moreover, the basis of each production from primary and secondary sources was explained to shows how they compliant with Sharīʿah. In addition, it mentioned the model of deposit products in Islamic banking that represented as wadī‘ah, qarḍ Hassan and muḍārabah that are replicate of conventional banking. Furthermore, it highlights the relationship between the depositor and depositee, as well as the obligations of both parties. The study argued that the adoption of the conventional banking structural practices by the Islamic banking is valid especially area of deposit and investment, since this account can be devoid of the interest element, Islamic banks are permitted by Sharīʿah to offer similar facilities.